Infrastruktur e-business sekolah tinggi Di pagar alam - Buhori Muslim (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2017)
in improving the quality of competition with competitors, colleges must be equipped with information technology infrastructure support, top management as decision makers need something that can push the system to compete with other universities, they need knowledge of information technology (IT) that can Supporting it in order to predict ahead and help the whole system to improve service. Business intelligence as a decision-making system that can help management with something that can be predicted and decided. Universities need an infrastructure design to create a solid foundation for business intelligence implementation that will be implemented on the internet or e-business.